CONCEPTUAL DESIGN APPROACH OF FARM MILK CHILLER (International Journal of Engineering Sciences & Management Research, 2016)
India is the largest milk producer as well as consumer of milk and milk products play significant role in Indian diet and are the most acceptable source of animal protein for large vegetarian segment of Indian population. Effective on-farm cooling of milk and maintenance of low temperature while transporting it from milking centre to collection centre is very important to ensure the quality of milk. To design an effective cooling system for on farm cooling of milk, there is a need to focus on some parameters like cooling rate, hygiene conditions, ergonomic features, etc. The present paper is an attempt to discuss the approach for designing a workable, easy to handle, low cost and sturdy farm milk chiller for maintaining the milk quality and cool chain during the initial stage of milk handling.